The conversion of CESR to operate as the Test Accelerator, CesrTA. Part 3: electron cloud diagnostics. (28th April 2016) - Billing, M.G.; Conway, J.V.; Crittenden, J.A.; Greenwald, S.; Li, Y.; Meller, R.E.; Strohman, C.R.; Sikora, J.P.; Calvey, J.R.; Palmer, M.A.
Abstract: Cornell's electron/positron storage ring (CESR) was modified over a series of accelerator shutdowns beginning in May 2008, which substantially improves its capability for research and development for particle accelerators. CESR's energy span from 1.8 to 5.6 GeV with both electrons and positrons makes it ideal for the study of a wide spectrum of accelerator physics issues and instrumentation related to present light sources and future lepton damping rings. Additionally a number of these are also relevant for the beam physics of proton accelerators. This paper is the third in a series of four describing the conversion of CESR to the test accelerator, CESRTA. The first two papers discuss the overall plan for the conversion of the storage ring to an instrument capable of studying advanced accelerator physics issues [1] and the details of the vacuum system upgrades [2]. This paper focusses on the necessary development of new instrumentation, situated in four dedicated experimental regions, capable of studying such phenomena as electron clouds (ECs) and methods to mitigate EC effects. The fourth paper in this series describes the vacuum system modifications of the superconducting wigglers to accommodate the diagnostic instrumentation for the study of EC behavior within wigglers. While the initial studies of CESRTA focussed on questions related to the International Linear Collider damping ring design, CESRTA is a very versatile storage ring, capable of studying a wide range of accelerator physics and instrumentation questions.